2019–2020 Florida Citrus Production Guide: Soft-Bodied Insects Attacking Foliage and Fruit - Lauren Marie Diepenbrock; Lukasz Stelinski; Jawwad Qureshi; Phil Stansly (EDIS, 2019)
This 5-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. This section is focused on sucking insects that affect foliage, twigs, and fruit of citrus in Florida. Insects covered here include scales, mealybugs, whiteflies, and aphids, which can all impact the health of both young and mature trees and their fruit quality. These insects differ from each other in their biology, generation times, and injury to plants, but approaches to monitoring and management are similar. Individual discussions of some groups are provided, and the tables of management options are organized by active ingredient, with the target pests from this chapter in bold text. Written by Lauren Marie Diepenbrock, Lukasz Stelinski, Jawwad Qureshi, and Phil Stansly, and published by the Entomology and Nematology Department, March 2019.